Article Review: The Role of Synbiotic Beverages Containing Purple Sweet Potato and Butterfly Pea Flower (Clitoria ternatea L.) as Functional Nutrition in the Management of Gestational Diabetes Mellitus - Risty Fadella; Arya Ulilalbab; Nining Tyas Triatmaja (Ficco Scientific Corner, 2026)
Background: Gestational diabetes mellitus is a common metabolic disorder during pregnancy that is associated with insulin resistance and increased oxidative stress. Functional nutrition through synbiotic beverages offers a promising non-pharmacological strategy to support glucose regulation and metabolic balance. Methods: A literature study was conducted by reviewing scientific articles obtained from Scopus, PubMed, SINTA, and Google Scholar databases. The analysis focused on bioactive anthocyanin compounds, probiotic-prebiotic synergies, as well as their effects on glucose metabolism and gut health. Results: Purple sweet potatoes and telang flowers contain anthocyanins with antioxidant, anti-inflammatory, and antihyperglycemic properties. Synbiotic formulations that combine these ingredients with probiotics such as Lactobacillus plantarum improve the composition of the gut microbiota and the production of short-chain fatty acids, thereby improving insulin sensitivity and glucose tolerance. Conclusion: A synbiotic drink made from purple sweet potato and telang flower shows strong potential as a functional nutritional intervention for DMG. Further clinical research is needed to ensure its safety and effectiveness in pregnant women.